A Life Cycle Assessment on Various Alternative Liquid Fuel Options in Western Australia - Wang, Lan Zhen (Curtin University, 2020)
This thesis assesses the life cycle energy, water and carbon footprints of several biofuels production processed, considering (a) biomass from phase farm with trees; (b) biodiesel from waste cooking oil with utilising the by-product (crude glycerol); and ( c) bioslurry from biochar bio-oil and crude glycerol.